Is Skill Type the Key to the PreK Fadeout Puzzle? Differential Associations Between Enrollment in PreK and Constrained and Unconstrained Skills Across Kindergarten. Issue 4 (9th January 2021) - McCormick, Meghan; Weiland, Christina; Hsueh, JoAnn; Pralica, Mirjana; Weissman, Amanda K.; Moffett, Lillie; Snow, Catherine; Sachs, Jason
Abstract : This study examines whether associations between enrollment in public and non‐public PreK and children's ( N = 508; M age = 5.60 years in fall of kindergarten) math and language and literacy outcomes were more likely to be sustained through the spring of kindergarten for unconstrained versus constrained skills. Associations between public PreK and language, literacy, and math outcomes were more strongly sustained through the spring of kindergarten for unconstrained skills, relative to constrained skills. Only associations between non‐public PreK and unconstrained language skills were sustained through the spring of kindergarten. Associations in the fall of kindergarten differed by family income and dual language learner (DLL) status but there was no subgroup variation by the spring of kindergarten. Implications for policy and practice are discussed.